Pengaruh Latihan Lari dan Lompat Tali dengan Interval Rasio Kerja Istirahat 1:1 dan 2:1 Terhadap Kebugaran Jasmani Peserta Didik SDN-2 Pendang - Jam'anor Jam'anor; Sigit Nugroho (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to determine the effect of two types of exercises, namely running and jump rope exercises with work-to-rest ratios of 1:1 and 2:1, on the improvement of physical fitness among students at SDN 2 Pendang. The method used in this study is an experiment with a quantitative approach through a 2x2 factorial design. The sample consisted of 20 students divided randomly into four exercise groups: (1) running exercise with a work-to-rest ratio of 1:1, (2) running exercise with a ratio of 2:1, (3) jump rope exercise with a ratio of 1:1, and (4) jump rope exercise with a ratio of 2:1. The research instrument to measure students' fitness used the SPN test. Data analysis technique used two-way ANOVA test to determine significant differences between experimental groups in improving physical fitness. The significance level used was α = 0.05. The research results showed that both types of exercises had a positive effect on improving physical fitness. However, exercises with a work-to-rest ratio of 2:1 provided more significant improvement compared to the 1:1 ratio, both in running and jump rope exercises. The highest improvement occurred in the jump rope exercise group with a 2:1 ratio, which showed high effectiveness in improving cardiovascular endurance and movement coordination. The comparison between running and jump rope exercises showed that jump rope had a more comprehensive impact on various aspects of physical fitness such as flexibility, leg muscle strength, and explosive power. Meanwhile, running exercise was more dominant in improving cardiorespiratory endurance. Considering the physical characteristics of elementary school children, interval training with a work-to-rest ratio of 2:1 was found to be more appropriate as it provided sufficient recovery time, allowing for more intensive exercise without causing excessive fatigue. Keywords: Interval, Physical Fitness, Exercise, Running, Jump Rope